Efficient and Reusable Metal–Organic Framework Catalysts for Carboxylative Cyclization of Propargylamines with Carbon Dioxide. Issue 24 (27th November 2017) - Zhao, Dan; Liu, Xiao‐Hui; Zhu, Chendan; Kang, Yan‐Shang; Wang, Peng; Shi, Zhuangzhi; Lu, Yi; Sun, Wei‐Yin
Abstract: Carbon dioxide (CO2 ) capture and transformation are important for decreasing the concentration of atmospheric CO2 . To effectively capture CO2 and further fix it into valuable chemical products, functionalized dynamic metal–organic frameworks (MOFs) have been utilized not only because of their inherent cavity for accommodating CO2 but also owing to their reversible structural transformations in response to external stimuli for regulating the reaction. Herein, we report a dynamic and functional MOF [Cd3 (L)2 (BDC)3 ]2 ⋅ 16 DMF (MOF‐1 a ; DMF= N, N ‐dimethylformamide) achieved by reaction of the amino tripodal imidazole ligand N 1 ‐(4‐(1 H ‐imidazol‐1‐yl)benzyl)‐ N 1 ‐ (2‐aminoethyl)ethane‐1, 2‐diamine (L) and 1, 4‐benzenedicarboxylic acid (H2 BDC) with cadmium salt. MOF‐1 a not only shows unprecedented high catalytic activity [initial turnover number (TON) up to 9300] and broad substrate scope for the carboxylative cyclization of propargylamines with CO2, but also can be switched on and off upon reversible structural transformation owing to its dynamic five‐fold interpenetrating structure. Further studies demonstrate that MOF‐1 a shows selective catalytic properties depending on the size of substrates, similarly to sophisticated biological systems. Abstract : Capture and transform it : The construction of a flexible and switchable 3D MOF‐1 a is described, which is decorated with NH2 groups and can not only realize the capture of CO2 but also demonstrates selective heterogeneous catalytic properties depending on the size of the catalytic substrates, in a similar way to sophisticated biological systems.